Erasmus bilateral agreement form for the academic year 2014/2020 Lifelong Learning Programme: higher education - Erasmus between Universidade Lusíada de Lisboa and Universidad de Valladolid - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Architecture and building.